Competing Top-Down Processes in Visual Selection: Evidence That Selection by Location Is Stronger Than Selection by Color. - Grabbe, Yvonne; Pratt, Jay (Journal of General Psychology, 2004)
The purpose of this study was to examine whether color and position information are functionally equivalent when observers are asked to select simultaneously on both dimensions. Observers were asked to report a letter of a given color from a given region of a briefly flashed letter array, then to report any additional letters they could recall from the stimulus set. Of the additional letters, more location letters were reported than were same-color or neutral letters. The results suggested that position information has priority over color information in top-down-guided visual selection. Reprinted by permission of the publisher.